Biorenewable, transparent, and oxygen/moisture barrier nanocellulose/nanochitin-based coating on polypropylene for food packaging applications. (1st November 2021) - Nguyen, Hoang-Linh; Tran, Thang Hong; Hao, Lam Tan; Jeon, Hyeonyeol; Koo, Jun Mo; Shin, Giyoung; Hwang, Dong Soo; Hwang, Sung Yeon; Park, Jeyoung; Oh, Dongyeop X.
Abstract: Aluminum-coated polypropylene films are commonly used in food packaging because aluminum is a great gas barrier. However, recycling these films is not economically feasible. In addition, their end-of-life incineration generates harmful alumina-based particulate matter. In this study, coating layers with excellent gas-barrier properties are assembled on polypropylene films through layer-by-layer (LbL) deposition of biorenewable nanocellulose and nanochitin. The coating layers significantly reduce the transmission of oxygen and water vapors, two unfavorable gases for food packaging, through polypropylene films. The oxygen transmission rate of a 60 μm-thick, 20 LbL-coated polypropylene film decreases by approximately a hundredfold, from 1118 to 13.10 cc m −2  day −1 owing to the high crystallinity of nanocellulose and nanochitin. Its water vapor transmission rate slightly reduces from 2.43 to 2.13 g m −2  day −1 . Furthermore, the coated film is highly transparent, unfavorable to bacterial adhesion and thermally recyclable, thus promising for advanced food packaging applications. Highlights: Nanocellulose and nanochitin are coated layer-by-layer on polypropylene films. The coating layers are a high oxygen barrier and highly transparent. The coated film shows reduced bacterial adhesion and good thermal recyclability. The coated polypropylene film can function as an advanced food packaging material.